Treatment recommendations for non-HIV associated cryptococcal meningoencephalitis including management of post-infectious inflammatory response syndrome - Ssebambulidde, Kenneth; Anjum, Seher H.; Hargarten, Jessica C.; Chittiboina, Prashant; Shoham, Shmuel; Seyedmousavi, Seyedmojtaba; Marr, Kieren A.; Hammoud, Dima A.; Billioux, Bridgette Jeanne; Williamson, Peter R. (Frontiers in Neurology, 2022)
Cryptococcal meningoencephalitis (CM) continues to cause major morbidity and mortality in a range of patients such as those immunosuppressed from HIV and with biologic immunosuppressants, including treatments of autoimmunity, malignancies, and conditioning regimens for transplantation. It is currently the most common cause of non-viral meningitis in the United States. Infections in previously healthy patients also develop with autoantibodies to granulocyte-macrophage colony stimulating factor or with monogenetic defects. In all populations, mortality and significant long-term morbidity occur in 30–50% despite therapy, and immune reconstitution and post-infectious inflammatory response syndromes complicate management. To help with these difficult cases, we present here a practical tutorial of the care of a range of patients with CM in the absence of HIV/AIDS.